Comparing private security regulation in the European Union. (4th May 2018) - Button, Mark; Stiernstedt, Peter
ABSTRACT: This paper examines the regulatory systems for the private security industry in the European Union (EU). Building upon other studies to compare regulatory systems it proposes a much more sophisticated approach to assess the quality of regulatory systems using 22 different criteria based on two areas: legislation and societal foundations. From this analysis a maximum of 100 points are possible and the paper is able to rank 26 of the 28 member states of the EU. The league table ranks Belgium and Spain as having the most comprehensive regulatory systems in the EU. The paper then provides analysis of some of the key findings from the league table noting some of the implications. One of the most important of which is the substantial differences between member states and the challenges this poses for an effective single market in the provision of security services.